Predação de morcegos (Phyllostomidae) pela cuíca d’água Chironectes minimus (Zimmermann, 1780) (Didelphimorphia, Didelphidae) e uma breve revisão de predação em Chiroptera - Bosco Breviglieri, Crasso Paulo; Pedro, Wagner Andre (My University, 2010)
Bats are predated for some of vertebrates and invertebrates. Some opportunistic species preys these animals' prisoners in nests during procedures of capture in field. This study records the predation of Carollia perspicillata (Linnaeus, 1758) and Sturnira lilium (E. Geoffroy, 1810) for Chironectes minimus (Zimmermann, 1780) on riparian forest of the brook Talhadinho belonging of the São Paulo, São Paulo, Southeast Brazil, and also presents a lifting previous of mammalian what they present the same one behavior opportunistic predatory, discussing measures simple to avoid this type of predation.
Predation of bats (Phyllostomidae) captured in mist nets for Chironectes minimus (Zimmermann, 1780) and lifting previous on the subject of predators what present the same behaviour.